Schisandra chinensis extract ameliorates nonalcoholic fatty liver via inhibition of endoplasmic reticulum stress. (5th June 2016) - Jang, Min-Kyung; Nam, Jeong Soo; Kim, Ji Ha; Yun, Ye-Rang; Han, Chang Woo; Kim, Byung Joo; Jeong, Han-Sol; Ha, Ki-Tae; Jung, Myeong Ho
Abstract: Ethnopharmacological relevance: Schisandra chinensis ( Turcz. ) Baill. (SC) is a traditional Chinese herbal medicine with diverse pharmacological activities for treatment of various human diseases. Endoplasmic reticulum (ER) stress is associated with the pathogenesis of nonalcoholic fatty liver disease (NAFLD). In this study, we investigated the protective effects of methanol extract of Schisandra chinensis (SC extract) against ER stress-induced NAFLD in vitro and in vivo . Material and methods: The protective effects of SC extract were examined in tunicamycin- or palmitate-treated HepG2 cells in vitro, and in tunicamycin-injected mice or high fed diet (HFD) obese mice in vivo . Expression of ER stress markers including glucose regulated protein 78 (GRP78), C/EBP homolog protein (CHOP), and X-box-binding protein-1 (XBP-1), and triglyceride accumulation were measured in HepG2 cells and in the liver of mice. Results: SC extract significantly inhibited expression of tunicamycin-induced ER stress markers in tunicamycin-treated HepG2 cells and in the liver of tunicamycin-injected mice, and it also inhibited tunicamycin-induced triglyceride accumulation. Similar observations were made under physiological ER stress conditions such as in palmitate-treated HepG2 cells and in the liver of HFD obese mice. In addition, SC extract repressed the expression of inflammatory genes and lipogenic genes in palmitate-treated HepG2 cells. Schisandrin, an abundant bioactive lignan in SC extract, inhibited the expression of ER stress markers in tunicamycin-or palmitate-treated HepG2 cells, whereas Gomisin J did not affect ER stress markers. Conclusions: SC attenuates ER stress and prevents development of NAFLD. SC may be useful as a pharmacological agent for protection against ER stress-induced human diseases. Graphic abstract: